Innovations in insuring the poor: Intelligent design of index insurance for smallholder farmers and pastoralists - Carter, Michael R. (International Food Policy Research Institute, 2009)
Despite their compelling logic, index insurance contracts that transfer risk from smallholder farmers and pastoralists have met with sometimes indifferent demand and low uptake by the intended beneficiaries. Yet the evidence that risk plays an important role in creating and perpetuating rural poverty is mounting and demands further efforts to solve this problem. This brief focuses on ways to solve this demand problem by designing index insurance contracts more intelligently.